TENDENCIES OF BORDER GUARDS EDUCATION SYSTEM QUALITY IN LATVIA - Gaveika, Artūrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The novelty of the research is related to the need of Latvia as a member of the European Union and the Schengen area to continuously improve the requirements of vocational education, competence and professional qualification of border guards. The main objective of the research is to summarize the views of border guards on the positive achievements of the existing education system and the shortcomings detected for further improvement of the education system of border guards. The aim of the research is to summarize the views of border guards on the necessity of the vocational education including practical classes and training courses in the education system and possible solutions for further improvement, as well as the development of profession standards in a new quality and to develop cooperation between EU countries and neighboring countries to obtain knowledge and practical skills. The method of legal analysis was implemented by analyzing the requirements of the normative regulation concerning the professional qualification of border guards, the historical analysis method was used to explore the evolution of the professional education of border guards in the historical aspect, as well as the survey (questionnaire) method performing the survey of border guards of different educational levels has been performed. The research uses legal analysis, historical and survey methods. As a result of the research valuable information has been obtained that will serve to improve border guards profession and education standards. Since October 2017, the Rēzekne Academy of Technology continues to implement the long-term studies initiated by the European Regional Development Fund's Postdoctoral Research Support Project "EU External Border Security, Latvia's Internal Security" No. 1.1.2 / VIAA / 1/16/127. The cooperation partner of the project is the State Border Guard College.